Growing together integrating community-managed hydroponic urban farming and co-living in a housing complex for Sitio San Roque - Lopez, Ivan Leroy L. (College of Architecture, University of the Philippines Diliman, 2025)
In addressing the livelihood challenges of off-city resettlement strategies for informal settler families (ISFs), this research proposes an alternative architectural solution: a medium-rise, housing complex integrating co-living with urban farming. Focused on Sitio San Roque, the project aims to provide sustainable, livelihood-inclusive housing without displacing residents from urban centers. Through a two-phase process - first constructing a universal design framework, then contextualizing it through Sitio San Roque’s socio-spatial realities - the study merges co-living spatial strategies with urban farming systems. The research draws on Save Sitio San Roque Alliance’s (SSRA’s) Community Development Plan (CDP) and targeted key informant interviews, replacing broader surveys with direct community data. The resulting architectural model demonstrates that integrating urban farming into residential structures can sustain both food security and income generation, while co-living configurations enhance space efficiency and strengthen community ties. The final design offers a replicable, low-energy, socially responsive alternative to conventional relocation housing models